Novel Word Learning: Event-Related Brain Potentials Reflect Pure Lexical and Task-Related Effects - Bermúdez-Margaretto, Beatriz; Beltrán, David; Cuetos, Fernando; Domínguez, Alberto (Frontiers in Human Neuroscience, 2019)
Previous research has pointed out that the combination of orthographic and semantic-associative training is a more advantageous strategy for the lexicalization of novel written word-forms than their single orthographic training. However, paradigms used before involve explicit stimuli categorization (lexical decision), which likely influence word learning. In the present study, we used a more automatic task (silent reading) to determine the advantage of the associative training, by comparing the brain electrical signals elicited in combined (orthographic and semantic) and single (only orthographic) training conditions. In addition, the learning effect (in terms of similar neurophysiological activity between novel and known words) was also tested under a categorization paradigm, enabling to determine the possible influence of the training task in the lexicalization process. Results indicated that novel words repeatedly associated with meaningful cues showed a higher attenuation of N400 responses than those trained in the single orthographic condition, confirming the higher facilitation in the lexico-semantic processing of these stimuli as a consequence of semantic associations. Moreover, only when the combined training was carried out in the reading task, did novel words show similar N400 responses as those elicited by known words, suggesting the achievement of a similar lexical processing to known words. Crucially, when the training is carried out under a demanding task context (lexical decision), known words exhibited positive enhancement within the N400 time window, contributing to maintain N400 differences with novel trained words and confounding the outcome of the learning. Such deflection —compatible with the modulation of the categorization-related P300 component— suggests that novel word learning could be influenced by the activation of categorization-related processes. Thus, the use of low-demand tasks arises as a more appropriate approach to study novel word learning, enabling the build-up process of mental representations which probably depends on pure lexical and semantic factors rather than being guided by categorization demands.